(untitled) (PANGEEA, 2025)
Known as an important occurrence of gold, at Pianu native platinum has been also found as early as 1855. The platinum contains also Fe (about 9%), a common fact for platinum occurrences. As a source for platinum the ultrabasic rocks (most serpentinites) have been considered, widely distributed in the Sebeş Mts., however not direclty occurring in the catchment area of the Pianu Valley.